Imagery ability in Boccia: comparison among federate athletes from different medical sport groups - Amorim, André (2017)
The aim of this study was to analyse and compare movement visualization ability in federate and non-federate Boccia athletes, and among federate Boccia medical sport groups. Forty-two Boccia athletes (Federate N = 24; Non-federate N = 18) at an average age of 35.8 (SD = 11.19) participated in this study. The Portuguese version of Movement Imagery Questionnaire - 3 (MIQ-3), was used for this study. The participants were evaluated on the internal and external visual imagery. Statistics was carried out following the method of interference based on the magnitude of the effects. Results showed a great effect of expertise in imagery ability. The comparison between federate and non-federate Boccia athletes showed a great effect in the Internal Visual subscale and a moderate effect in the External Visual subscale. It was also observed differences between athletes from different medical-sports groups, revealing that the requirements of the sport linked to their action abilities provides them with different Imagery abilities. These results clearly influence the prescription of imagery training programs for different groups taking into account different medical-practice groups.